Increase okra production with the addition of nitrogen: Increase okra productivity with the addition of nitrogen - Coutinho-Miranda, Valdilene; Pascual-Reyes, Irais Dolores; Torquato-Tavares, Aline; Gonçalves-Carline, João Victor; Silva-Sousa, Kássio Abel; Rodrigues-do-Nascimento, Ildon (Agronomía Mesoamericana, 2019)
Introduction. The growth, production, and quality of the okra (Abelmoschus esculentus (L.) Moench) are related to the application of fertilizers with nitrogen (N) being the most prominent, due to the direct relationship with photosynthesis and vegetative growth of the plant. Objective. The objective was to evaluate the agronomic and productivity characteristics of the okra based on the dose of N. Materials and methods. The study was carried out in the experimental area Campus Gurupi, of the Universidad Federal de Tocantins (UFT), in two planting periods (autumn/winter and spring/summer). The experimental design used was randomized blocks (DBC) with six treatments (0, 50, 100, 150, 200, and 250 kg N ha-1) and four repetitions. Urea was used as a source of N. The characteristics evaluated were: productivity, average fruit mass, height and chlorophyll index of the plant. Results. The productivity and height of the plant were higher in the autumn/winter crop. The average mass and chlorophyll index were not influenced by the sowing period. For productivity a linear response was obtained, increasing the dose up to the limit of the dose of N used (250 kg ha-1), with an average value higher than 14 t of fruit. The mean mass and plant height responded linearly to the increase in the dose of N. Nitrogen affected the chlorophyll index, with maximum values of 45.96 and 47.19, observed in the two evaluation periods. Conclusion. The sowing season and the N content in the soil interacted with the height of the plant, being favorable in the period when there was no precipitation. N influenced all characteristics, demonstrating the importance of nitrogen fertilization development okra plants.